2024
DOI: 10.1088/1742-6596/2736/1/012031
|View full text |Cite
|
Sign up to set email alerts
|

The Development of New Type GFRP Hollow Panels

Yuxin Wei,
Zhiping Wang,
Junzheng Xiang
et al.

Abstract: Under the background of global energy transformation, pumped storage power stations are becoming more and more important. Most of their water retaining structures adopt face rockfill dams, but their concrete panels will have many problems such as durability. In this study, a new type of GFRP hollow panel was developed for face rockfill dam. The nonlinear behavior and damage process of the material were simulated by finite element analysis and UMAT subroutine. Through analysis and comparison, it is found that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…A new type of GFRP hollow panel was developed to face a rockfill dam by Wei Y (2024). They simulated the nonlinear behavior and damage process of the material by finite element analysis and UMAT subroutine and found that the triangular section form is superior to other forms in terms of stress distribution and bearing capacity [8]. In order to improve the structural integrity and blast resistance of RC beams, rubberized steel fiber-reinforced concrete beams were proposed by Mahmoud T. Nawar (2024) [9].…”
Section: Introductionmentioning
confidence: 99%
“…A new type of GFRP hollow panel was developed to face a rockfill dam by Wei Y (2024). They simulated the nonlinear behavior and damage process of the material by finite element analysis and UMAT subroutine and found that the triangular section form is superior to other forms in terms of stress distribution and bearing capacity [8]. In order to improve the structural integrity and blast resistance of RC beams, rubberized steel fiber-reinforced concrete beams were proposed by Mahmoud T. Nawar (2024) [9].…”
Section: Introductionmentioning
confidence: 99%